Information of Covid-19 and its Impact on Stock Return - Marcello Johanes; Liza Handoko (Fakultas Ekonomi Dan Bisnis Universitas Pelita Harapan, 2022)
This paper study the impact of information on the internet regarding Covid-19 and vaccination on the stock return. The pandemic itself has affected the world in every sector and market, including the stock market. Investors take information from the internet to make investment decision and during pandemic covid-19 and vaccination are the interest of investors around the world. This research takes sample of Indonesia, Malaysia, Singapore, and Thailand’s stock market return from March 2020 until February 2022. This study applied random effect to test the model. Findings from this research show that GSV (Google Search Volume) of Covid and Vaccine simultaneously didn’t affect the stock return. However, GSV Vaccine has positive impact on Indonesian stock return.